Pengaruh Kualitas Layanan dan Harga terhadap Kepuasan Pelanggan JNE Pusat di Tomang Jakarta Barat - Pribadi, Sulistya; Setyawati, Aswanti; Muldiansyah, M. Iqbal (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
Logistics services are fast-growing services due to the flow of information and goods, as well as higher consumption needs. This is also due to the development of the e-commerce business and people's desire to make transactions more practical and economical. PT. Tiki Jalur Nugraha Ekakurir (JNE), located in Tomang, West Jakarta, is a logistics service company that provides services for domestic and international goods delivery. JNE is always committed to providing the best service to achieve integrity and satisfying quality for its customers. This study aims to analyze the effect of service quality and price on customer satisfaction at JNE Pusat. The research method is quantitative, using a questionnaire distributed to 109 respondents who are JNE Pusat customers. The data is processed using SPSS 29, with instrument testing using validity and reliability tests. The methods of data analysis used are simple linear regression, multiple linear regression, t-test, f-test, and the coefficient of determination.The results of this study indicate that service quality and price have a positive and significant effect on customer satisfaction, with a determination coefficient of 58%. This means that 42% of customer satisfaction is influenced by other factors.